2013
DOI: 10.1108/ijlbe-11-2012-0025
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of implementation of the Energy Performance of Buildings Directive in the Mediterranean

Abstract: Purpose -The Energy Performance of Buildings Directive (EPBD) 2002/91/EC introduced various obligatory requirements intended to achieve the reduction of use of energy resources in buildings. This directive had to be transposed into national legislation by the EU member states. Concurrently the European Committee for Standardisation developed a number of technical standards to assist member states to define the methodology for the calculation of the energy performance of buildings. The purpose of this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In two earlier studies, EPBD: 2002/91/EC introduced various obligatory requirements intended to achieve the reduction of use of energy resources in buildings. It was proven that the relationship between the EPBD and milder climates experienced in the Mediterranean is considered to be of great importance, particularly since world temperatures are slowly rising [27,28]. Burman et al [28] introduced a methodology to calculate energy performance of buildings, with its theoretical performance using calibrated thermal modelling, under standardized operating conditions.…”
Section: Literature Background Upon Indoor Environmental Quality and mentioning
confidence: 99%
See 2 more Smart Citations
“…In two earlier studies, EPBD: 2002/91/EC introduced various obligatory requirements intended to achieve the reduction of use of energy resources in buildings. It was proven that the relationship between the EPBD and milder climates experienced in the Mediterranean is considered to be of great importance, particularly since world temperatures are slowly rising [27,28]. Burman et al [28] introduced a methodology to calculate energy performance of buildings, with its theoretical performance using calibrated thermal modelling, under standardized operating conditions.…”
Section: Literature Background Upon Indoor Environmental Quality and mentioning
confidence: 99%
“…However, in these earlier studies [27,28], it was also acknowledged that insufficient research has been carried out on the energy performance of buildings, at least among the Mediterranean basin countries. Therefore, Abela et al [27] investigated the existing legal structures that had been put into place to implement the EPBD and the effectiveness of this implementation to date (year 2013) to define the methodology for the calculation of the energy performance of buildings [27].…”
Section: Literature Background Upon Indoor Environmental Quality and mentioning
confidence: 99%
See 1 more Smart Citation
“…The European Energy Performance of Buildings Directive (EPBD), introduced in the 2000s, is the cornerstone of the efforts to achieve high energy performance in buildings and educate citizens on energy-saving practices to lower costs [31,32], a holistic approach that plays a crucial role in navigating the complexities of diverse energy technologies and sources. The initial version of the EPBD made the energy performance certificate a mandatory requirement for all European members, applicable to buildings under construction or undergoing selling and renting procedures [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of the European Commission's Internal Market Scoreboard, the EPBD was the worst performer in terms of transposition before the deadline date of May 2006 with nine countries (Belgium, Greece, France, Cyprus, Luxembourg, Hungary, Malta, Austria, Slovenia) failing to fully transpose the directive as at May 2008 [13]. A comparative analysis of progress towards implementation in the member states revealed significant diversity and found that only some member states managed to fully implement the directive with most countries still at the half way point [3] , and a small number still in the early stages of implementation [2]. Whilst the first EPBD was clearly a step in this direction, it became necessary for the European Commission to implement more concrete strategies to achieve the great unrealised potential for energy savings in buildings and to reduce the large differences between Member States' results in this sector [15].…”
Section: Introductionmentioning
confidence: 99%